Menumbuhkan Kesadaran Gizi Seimbang Melalui Edukasi dan Pengecekan Status Gizi pada Santriwati di Maahad Tahfiz Al-Qur’an Darul Falah, Selangor, Malaysia - Iiz Roizul Fahmi; Shinta Arviana; Imelda Puspitasari; Vika Safitri Rahmayuniar; Alicia Safina Rahma (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2024)
Maahad Tahfiz Al-Qur’an Darul Falah, Selangor, Malaysia, is an institution focused on Qur’an memorization for female students. Due to their intense activities, including memorization requiring high concentration, balanced nutrition is essential for supporting their academic performance and health. However, their nutritional intake has not been fully optimized. Initial observations indicated that some students have limited knowledge of balanced nutrition, which may affect their health and nutritional status. This community service program aimed to raise awareness about the importance of balanced nutrition through education, nutritional status checks, and counseling. The program included three main activities: (1) Nutrition education through lectures and interactive sessions, covering basic concepts of balanced nutrition, the food pyramid, and guidelines from the Ministry of Health Malaysia; (2) Nutritional status checks through height and weight measurements to calculate Body Mass Index (BMI), identifying students' nutritional categories and related issues; and (3) Nutritional counseling, conducted after the status checks, teaching students how to achieve or maintain an ideal weight and offering advice on healthy eating and lifestyle habits. The program, which involved 40 students, found that 60% of them had a normal nutritional status, while some were underweight (12.5%), overweight (20%), and obese (7.5%). The education and counseling sessions helped improve the students' understanding of the importance of balanced nutrition and provided guidance on how to maintain or achieve a healthy weight, supporting their overall health and academic.